2010
DOI: 10.1016/j.gca.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Two diffusion pathways in quartz: A combined UV-laser and RBS study

Abstract: The diffusive behavior of argon in quartz was investigated with three analytical depth profiling methods: Rutherford Backscattering Spectroscopy (RBS), 213 nm laser ablation, and 193 nm (Excimer) laser ablation on the same set of experimental samples. The integration of multiple depth profiling methods, each with different spatial resolution and sensitivity, allows for the cross-checking of methods where data ranges coincide. The use of multiple methods also allows for exploration of diffusive phenomena over m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 58 publications
(112 reference statements)
0
12
0
1
Order By: Relevance
“…Advances in laser spot and depth profile extraction techniques, and in stepped and cycle heating, have largely confirmed the Arrhenius relationship between diffusion rates and temperature (e.g. Foland 1974;Arnaud & Kelley 1997;Lovera et al 1997;Wartho et al 1999;Lovera et al 2002), although recent analyses of argon diffusion at submicron spatial resolution (Watson & Cherniak 2003;Thomas et al 2008;Baxter 2010;Clay et al 2010) appear to indicate more than one diffusion mechanism in silicates. In contrast to the general consensus over the relationship between diffusion rates and temperature, there has been considerable debate and uncertainty concerning argon-loss systematics resulting from complexity in sample microstructure, including perthite boundaries, subgrains, and fast diffusion pathways.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Advances in laser spot and depth profile extraction techniques, and in stepped and cycle heating, have largely confirmed the Arrhenius relationship between diffusion rates and temperature (e.g. Foland 1974;Arnaud & Kelley 1997;Lovera et al 1997;Wartho et al 1999;Lovera et al 2002), although recent analyses of argon diffusion at submicron spatial resolution (Watson & Cherniak 2003;Thomas et al 2008;Baxter 2010;Clay et al 2010) appear to indicate more than one diffusion mechanism in silicates. In contrast to the general consensus over the relationship between diffusion rates and temperature, there has been considerable debate and uncertainty concerning argon-loss systematics resulting from complexity in sample microstructure, including perthite boundaries, subgrains, and fast diffusion pathways.…”
mentioning
confidence: 95%
“…The diffusion parameters from these studies corroborated the accepted laboratory values of activation energy (E) and pre-exponential factor (D 0 ) for alkali feldspars and values determined by step heating and cycle heating of natural samples. While it has been implied that argon diffusion domains in Itrongay feldspar should equate to physical grain sizes, Arnaud & Kelley (1997) hypothesized fast-track diffusion in the outermost few microns, and other studies have measured varying laboratory diffusion and solubility in the outermost micron (Watson & Cherniak 2003;Thomas et al 2008;Baxter 2010;Clay et al 2010).…”
mentioning
confidence: 99%
“…This effect has been observed in other LADP experiments aimed at characterizing diffusive loss profiles (e.g., Wartho et al, 1999) and has been interpreted as an anomalous signal possibly related to sample preparation. Recent work by Clay et al (2010), utilizing both RBS and LADP, has also documented this phenomenon for Ar diffusion into quartz. Clay and colleagues suggest that the anomalously high near-surface Ar concentrations they measured represent the presence of two diffusion pathways with different energetics, and they suggest that the thickness of the abnormally Ar-enriched zone is too great to be explained simply by sample preparation effects.…”
Section: Derivation Of Diffusion Parameters From Ladp Datamentioning
confidence: 85%
“…Wartho et al (1999) employed a frequency-quadrupled Nd-YAG (266 nm) ultraviolet laser to characterize 40 Ar diffusion profiles in a K-feldspar from Madagascar by progressively ablating downward from the sample surface and analyzing the extracted gas after every few microns of drilling using a magnetic-sector mass spectrometer. Finally, Clay et al (2010) used a combination of RBS (Rutherford Backscattering Spectroscopy), with depth resolution comparable to ERDA and NRA, and LADP (both a 193 and 213 nm UV laser microprobe) to study diffusion of Ar into quartz. While the laser ablation depth profiling (LADP) technique has about two orders of magnitude poorer depth resolution than ERDA, NRA or RBS, it permits the quantification of deeper diffusion profiles in heat-treated materials and thus avoids possible compromise of the experimental results by near-surface structural defects produced by surface grinding and polishing during sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Argon is generally thought to be incompatible (K D mineral/melt << 1; Kelley, 2002) but some workers 456 (Clay et al 2010;Baxter et al, 2010 and references therein) have suggested that uptake of Ar in the 457 outermost portions (100s nm to 10s microns) of mineral surfaces may be significant (e.g., 1000's ppm 458 concentrations). Incorporation of excess Ar within these surfaces could account for the older apparent 459 ages.…”
Section: Erroneous Apparent Ages In Feldspar From Subglacial Rocks 44mentioning
confidence: 99%